Corporate Governance Practices in Large and Medium-Sized Auditing Firms in South Africa - Smith, Rozanne; Marx, Ben (International Journal of Management and Sustainability, 2022)
South African corporate failures and audit failures, including those of VBS Bank, Tongaat, Steinhoff and KPMG, have exposed vulnerabilities in audit quality and the role of governance failures in auditing firms. In auditing firms, good corporate governance principles are not always followed. Additionally, South Africa does not have a corporate governance code that governs auditing firms, nor is there a sector supplement to the King IV Report on Corporate Governance that applies to other industries. To identify areas for improvement in South Africa, this study aimed to ascertain the current corporate governance practices in South African auditing firms and compare them to the United Kingdom (UK) Audit Firm Governance Code. A structured questionnaire based on the UK Audit Firm Governance Code was used to collect qualitative data. Nine large and medium-sized South African auditing firms with 20 or more auditing partners made up the population. The literature study emphasised the value of good corporate governance in auditing firms, as well as the difficulties these firms encounter with corporate governance. The review also emphasised the absence of codes and standards regulating corporate governance in auditing firms. The empirical results highlighted the resultant inconsistencies in corporate governance application in South African auditing firms. Areas requiring improvement were identified in the study.